PERTANGGUNGJAWABAN PIDANA PENIPUAN OLEH PERUSAHAAN BIRO PERJALANAN HAJI DAN UMROH - Dimas Prayoga; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Business opportunities to hold umrah services are very interesting becausethe majority of the population of Indonesia is Muslim. Fraud cases carried out bythe Hajj and Umrah Travel bureau companies are not the only corporate criminalacts that occur in Indonesia, Fraud Cases of the First Travel Hajj and Umrahtravel agencies, Abutours, fraud cases of the Hajj and Umrah travel agents JoePentha Wisata, Fraud travel agency cases Hajj and Umrah, PT Solusi BaladLumampah (SBL). The rarity of corporations that are made as suspects ordefendants is certainly interesting to study and study.This type of research can be classified in normative legal research, namelylegal research conducted by researching library materials. This study examinesthe subject matter in accordance with the scope and identification of the problemthrough a statute approach carried out by examining the laws and regulationsthat relate to the legal issue under study. In this study the authors conducted astudy of the principles of law by utilizing descriptive methods. Data collectiontechniques used in the Normative Legal Research are library research methods(library research) which uses the library as a means of collecting data, bystudying books as reference material related to the problems to be studied.The conclusion that can be obtained from the results of the study isCriminal Crime Accountability by the Company Hajj and Umrah Travel Agenciesexperiencing obstacles. There is no uniformity of understanding among lawenforcement officials ranging from the police, prosecutors to the judiciary aboutthe criminal responsibility of the corporation. The Ideal Setting of Fraud CrimeAccountability by Hajj and Umrah travel agency companies must provide legalcertainty. The formulation of when a corporation can be said to commit a crimemust be clearly regulated, namely when the crime is carried out by people, eitherbased on work relations or based on other relationships, acting within thebusiness entity or in other words corporate crime can only occur when a personacts in a corporate environment both in work relations and other relationships,outside of these restrictions cannot be regarded as a corporate crime.Keywords: Criminal Liability, Corporations, Fraud, Hajj and Umrah TravelBureau